The Effect of Using Catfish and Cork Fish on the Quality of Fish Fingers - Wulandari, Melia; Anggraini, Ezi (Universitas Negeri Padang, 2023)
The needs of today's society are the availability of food that is ready to cook and ready to eat. One type of food innovation is frozen food such as fish finger.Fish finger is a processed fish product made from pieces (fish fillets) or fish meat or surimi which are then given spices, coated with batter flour (a mixture of several flours that function as coating materials and adhesives) and breadcrumbs (bread flour) as an outer layer which is then fried half-baked and frozen.This study aims to analyze the effect of using catfish and cork fish on the quality of the shape, color, texture, aroma and taste of fish finger. This type of research is a pure experiment (true experiment), using a completely randomized design (RAL) with 3 repetitions. The research was conducted in the Catering Workshop of the Department of Family Welfare Science, Faculty of Tourism. This research was conducted in January 2023 with three repetitions. The type of data used is primary data sourced directly from 3 expert panelists in the organoleptic test. Based on the results of the organoleptic test, it shows that there is no significant difference in the quality of fish fingers using catfish (X1) and cork fish (X2). The best overall score is the quality of uniform shape (X2) 3. The quality of the beam shape (X2) 3.22. Golden yellow color quality (X2) 3.89. Fragrant aroma quality (X2) 3.78. The quality of chewy texture (X2) is 3.44. Savory taste quality (X2) 3.44. Based on the data obtained, it can be observed that the quality of cork fish fingers is better than catfish fish fingers.